МЕТОДИЧНА РОБОТА У СИСТЕМІ ПРОФЕСІЙНОЇ ПІДГОТОВКИ ВЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2001)
The article deals with the main forms of methodic work of school which help to develop creative style of teachers’ activity.